Introductory immunology : Basic concepts for interdisciplinary applications - Jeffrey K Actor (Elsevier/Academic Press, 2014)
Introductory Immunology quickly acquaints readers with natural immune responses manifesting in diseases and disorders. The book presents a complete picture of natural defenses to infectious agents, as well as the mechanisms that lead to autoimmune dysfunction. In addition, it examines immunologically based diseases, giving the reader sufficient knowledge to make sound clinical decisions leading to better treatment outcomes. Introductory Immunology is aimed at researchers, postgraduates, or any scientifically inclined reader interested in immunology